2019
DOI: 10.3390/met9060683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron Beam Method on Processing of Titanium Technogenic Material

Abstract: This study reveals the efficiency of the electron beam processing of titanium technogenic material with a high level of impurities and the quality of the obtained metal in correlation to process parameters which are discussed. The influence of the beam power and melting time on the composition variation, morphologies, hardness of metal samples and mass losses is investigated. Based on the different technological parameters, the removal efficiency of impurities is also discussed, and the corresponding experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…(4) Due to the effect of continuous heat treatment during the deposition process, supersaturated alloy elements in the form of globular intermetallic compounds began to separate in large quantities from the interior of the grain in the middle of the as-deposited wall, which caused a great amount of Cr atoms to be consumed by the austenitic matrix, leading to the austenite grains in the upper region being etched deeper than those in the bottom and middle regions by the etching fluid. (5) The microhardness values changed along a concave parabola on the cross-section along the building direction, i.e., it decreased first and then rose. The influence of intermetallic compound precipitation on microhardness was greater than that of the change in grain size in the arc-deposited part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Due to the effect of continuous heat treatment during the deposition process, supersaturated alloy elements in the form of globular intermetallic compounds began to separate in large quantities from the interior of the grain in the middle of the as-deposited wall, which caused a great amount of Cr atoms to be consumed by the austenitic matrix, leading to the austenite grains in the upper region being etched deeper than those in the bottom and middle regions by the etching fluid. (5) The microhardness values changed along a concave parabola on the cross-section along the building direction, i.e., it decreased first and then rose. The influence of intermetallic compound precipitation on microhardness was greater than that of the change in grain size in the arc-deposited part.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this traditional manufacturing method cannot be used for some parts with extremely complex internal cavities and those requiring integrated forming [2]. Additive manufacturing technology [3][4][5][6] is drawing more and more attention in the industry because of its good adaptability to complex part production. However, most of the current wire arc additive manufacturing (WAAM) research is generally based on the traditional pulse current as the arc source, and the range of research mainly focuses on studying the influence of various process parameters such as current, voltage, and welding speed on molding appearance and mechanical properties [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that it is quite realistic when using EBM, as the processing happens in a vacuum, and powder inside the sealed cylinders does not have any encapsulated gases. This ap-proach is inspired by the recycling pathway using laser-or electron-beam-based equipment with simplified control of the beam used just for melting scrap material into ingots [171][172][173], but it has the advantage of conducting essentially full recycling at the manufacturing site without any need for costly and hazardous transportation of powders to a specialized recycling site. Repairing and remanufacturing using additive manufacturing [143,[178][179][180][181][182].…”
Section: Recycling Of Metal Powders For Additive Manufacturingmentioning
confidence: 99%
“…Methods such as laser, plasma and electron beam melting (EBM) are successfully applied following the development of modern metallurgy and effective methods for refining metals and alloys [ 9 , 10 , 11 ]. Of these methods, the EBM method is particularly appropriate as it combines the advantages of vacuum and high-energy special electrometallurgy [ 12 , 13 , 14 , 15 , 16 ]. Under vacuum conditions, some reactions take place that are impossible at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%